Inventory models with reverse logistics for assets acquisition in a liquefied petroleum gas company - Lopes, Cristina (2021)
This paper addresses a case study regarding inventory models for acquiring liquefied petroleum gas (LPG) cylinders. This is an industrial challenge that was proposed at an European Study Group with Industry, by a Portuguese energy company, for which the LPG cylinder is the main asset of its LPG business. Due to the importance of this asset, an acquisition plan must be defined in order to determine the amount of LPG cylinders to acquire, and when to acquire them, in order to optimize the investment. As cylinders are returned and refilled, the reverse logistic flows of these assets must be considered. As the classical inventory models are not suitable for this case study, three new inventory models, which account for the return of LPG cylinders, are proposed in this work. The first proposed model considers deterministic constant demand and continuous returns of LPG cylinders, with discrete replenishment from the supplier. The second model is similar, but for the case when the returnedcylinders cover for the demand. A third model is also proposed considering that boththe demand and the returns are stochastic in nature and the replenishment from thesupplier is discrete. The three models address different scenarios that the company iseither currently facing or is expecting to occur in the near future.